2023
DOI: 10.3390/vaccines11030560
|View full text |Cite
|
Sign up to set email alerts
|

Could Prior COVID-19 Affect the Neutralizing Antibody after the Third BNT162b2 Booster Dose: A Longitudinal Study

Abstract: Vaccination is an essential public health measure for preventing the spread of illness during this continuing COVID-19 epidemic. The immune response developed by the host or the continuation of the immunological response caused by vaccination is crucial since it might alter the epidemic’s prognosis. In our study, we aimed to determine the titers of anti-S-RBD antibody and surrogate neutralizing antibody (snAb) formed before and after the third dose of the BNT162b2 vaccination (on the 15th, 60th, and 90th days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…One study showed that antibody response to a COVID-19 vaccine at one and five months after primary vaccination was not affected by sex, while antispike IgG levels differed between women and men at three months postvaccination [ 17 ]. In addition, another study has reported no significant difference in antibody titers between men and women after the booster dose [ 47 ]. Differences regarding the impact of sex on antibody levels may be due to the coexistence of other host factors such as age and other comorbidities, and further clinical trials are necessary to determine and evaluate the impact of sex differences on the effectiveness of the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that antibody response to a COVID-19 vaccine at one and five months after primary vaccination was not affected by sex, while antispike IgG levels differed between women and men at three months postvaccination [ 17 ]. In addition, another study has reported no significant difference in antibody titers between men and women after the booster dose [ 47 ]. Differences regarding the impact of sex on antibody levels may be due to the coexistence of other host factors such as age and other comorbidities, and further clinical trials are necessary to determine and evaluate the impact of sex differences on the effectiveness of the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%